2013
DOI: 10.1007/s10549-013-2805-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of genes co-amplified with nicastrin in breast invasive carcinoma

Abstract: Breast cancer accounts for more than 450,000 deaths per year worldwide. Discovery of novel therapeutic targets that will allow patient-tailored treatment of this disease is an emerging area of scientific interest. Recently, nicastrin has been identified as one such therapeutic target. Its overexpression is indicative of worse overall survival in the estrogen-receptor-negative patient population. In this paper, we analyze data from a large invasive breast carcinoma study and confirm nicastrin amplification. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…5B ). When we looked at genes potentially co-amplified with PBX1 (chr1q23.3) [ 27 ] we found that very few candidates were also over-expressed in breast cancer ( Fig. S10A ).…”
Section: Resultsmentioning
confidence: 99%
“…5B ). When we looked at genes potentially co-amplified with PBX1 (chr1q23.3) [ 27 ] we found that very few candidates were also over-expressed in breast cancer ( Fig. S10A ).…”
Section: Resultsmentioning
confidence: 99%
“…Our results revealed that the cellular status of AKT1 might determine the magnitude of splice variance ( Figure 6 ). Interestingly, many of the examples of the top 10 highly dispersed splicing events affected by the status of AKT1 have been previously implicated in cancerous phenotypes [ 63 , 68 , 69 , 70 , 71 , 72 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ]. Though not in the top 10, we also found examples of AKT1-dependent transcripts that also underwent differential splicing in a manner dependent on the presence or silencing of AKT1.…”
Section: Discussionmentioning
confidence: 99%
“…These membrane proteins have not been reported in previous cervical cancer studies; however, published reports support their involvement in other cancer types, as shown in Table III. Nicastrin in particular is considered as a putative therapeutic target in breast cancer (25,26), and further investigation of its potential for cervical cancer therapy is warranted. Thus, the identified membrane proteins reveal novel perspectives for the molecular characterization of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent differentially expressed proteins (TMX2, FAM120A, CLPTM1, CKAP5 and NCSTN) that followed the same pattern of expression in all cancer cell lines are presented in Table III, along with information on their molecular function. Moreover, for these specific proteins, a literature search was performed on previous relevant studies describing their role in cancer biology (20)(21)(22)(23)(24)(25)(26), which was incorporated in Table III. IPA and PPI network. To further characterize the biological functions and pathways relevant to the differentially expressed proteins, IPA software was employed.…”
Section: Analysis Of Protein Differential Expression In the Siha Helamentioning
confidence: 99%